The Da’wah Way of Sunan Gunung Djati in Cirebon: Building Ethno-Religious Identity and Moderation Values in a Multicultural Society - Nandang, Kris; Ramdhani, Suciyadi (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
This article contains a study of Sunan Gunung Djati regarding his preaching (dakwah) in Cirebon where the people are multicultural. Through historical research methodology which is divided into three basic heuristic processes, interpretation and historiography, this paper aims to present descriptive-analytic writing through the contextualization of historical (past) and present values. The focus of this paper discusses the path of preaching Sunan Gunung Djati in Cirebon which in its history has built an ethno-religious society as an effort to harmonize religious and cultural values ​​that are in line with the values ​​of moderation. This study is a response to the conflicts that occur due to ethnic, racial, religious and intergroup sentiments which are a challenge for multicultural Indonesian society. The results of this study show that Sunan Gunung Djati played a major role as a religious and government leader in building the stability of his country and religion. There are at least three efforts that can be taken as steps to internalize the values ​​of moderation in Indonesia, namely regulation-based efforts, education-based efforts and socialization-based efforts.